Tracing the Criminal Policy on Castration and Community Response - Panggabean, Mompang L (Faculty of Law, Universitas Sebelas Maret, 2021)
The act of chemical castration is now one of the sanctions in Indonesia's positive law. However, it is still limited to child protection based on Law Number 17 of 2016, which can be imposed on perpetrators of sexual crimes against children if the victim is more than one person, is seriously injured, has mental disorders, suffers from infectious diseases, reproductive system disorders, and lose their life. This paper analyzes criminal policy and people's reactions to castration concerning the objectives of punishment. This research is doctrinal research as prescriptive research using a legal approach regarding legal categories regarding castration, the relationship between rules, difficulties that arise and predicting future developments on criminal policy regarding castration in positive law as one of the new sanctions in the criminal system. The results of the study is that the birth of chemical castration in criminal policy reform is based on a balance between the interests of child victims of sexual crimes and perpetrators of crime, but its existence in positive law does not necessarily make the whole community accept even though the pros and cons of castration are still balanced based on the purpose of punishment based on Pancasila. The recommendations put forward are the need for socialization of castration for all levels of society in a balance between the interests of child victims of sexual crimes and the interests of criminals, increasing non-penal efforts and the application of selective castration sanctions, and providing assistance for child victims of sexual crimes.